2008
DOI: 10.1159/000139991
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control and Symptomatic Intradialytic Hypotension in Diabetic Haemodialysis Patients: A Cross-Sectional Survey

Abstract: Background:Cardiovascular disease remains the most common cause of mortality in end-stage kidney failure patients with diabetes. To improve blood pressure control, and reduce cardiovascular risk, in 2002 the UK Renal Association Standards’ Committee introduced pre- and post-dialysis target blood pressures of <140/90 and <130/80 mm Hg, respectively. Methods: We audited blood pressure control and symptomatic intradialytic hypotension during 1 week in the eleven renal centres in the Greater London Urban Area in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 29 publications
(21 reference statements)
4
44
0
Order By: Relevance
“…Diabetic patients have increased thirst [7], and a recent multi-centre study showed that diabetic haemodialysis patients were more likely to have greater inter-dialytic weight gain than nondiabetics [8], which is in keeping with an earlier report showing that diabetic control was linked to inter-dialytic weight gain [9]. Multi-frequency bioimpedance has been validated as an objective measure of fluid and nutritional status in dialysis patients.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Diabetic patients have increased thirst [7], and a recent multi-centre study showed that diabetic haemodialysis patients were more likely to have greater inter-dialytic weight gain than nondiabetics [8], which is in keeping with an earlier report showing that diabetic control was linked to inter-dialytic weight gain [9]. Multi-frequency bioimpedance has been validated as an objective measure of fluid and nutritional status in dialysis patients.…”
Section: Introductionmentioning
confidence: 68%
“…Previous studies in haemodialysis patients have reported that diabetic dialysis patients have greater inter-dialytic weight gain [8], and that those patients with poor diabetic control, as assessed by HbA1c, had greater inter-dialytic weight gain [18]. This may be due to the fact that diabetic patients with poor diabetic control and high HbA1c values may have increased thirst [7].…”
Section: Discussionmentioning
confidence: 99%
“…There has been debate as to the effect of increasing glucose concentrations on the measurement of serum sodium using indirect potentiometer and flame photometry [14], and potential correction factors for adjusting serum sodium for glucose, with some studies reporting no difference in serum sodium concentration between diabetic and non-diabetic dialysis patients [6,15]. Previous observational studies have suggested greater inter-dialytic weight gains in diabetic patients [16], and greater ratio of extracellular to total body water in diabetic peritoneal dialysis patients [17], suggesting that hyponatraemia in diabetic dialysis patients may have an over hydration component, perhaps due to increased thirst. However, when we repeated our analyses after excluding those patients who had diabetes as the primary cause of end-stage kidney disease, the association between lower serum sodium and mortality remained, as did the effect of age.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the higher weight gains, intradialytic hypotension was increased in the diabetic patients [9]. As there may be potential confounding factors in multi-centre studies, such as differing dietetic and educational input and dialysate sodium concentrations, we decided to prospectively audit interdialytic weight gains in a single centre to determine whether there was any association between diabetic control and interdialytic weight gains.…”
Section: Introductionmentioning
confidence: 99%